Performance of optimised SCR retrofit buses under urban driving and controlled conditions. (March 2015) - Carslaw, David C.; Priestman, Max; Williams, Martin L.; Stewart, Gregor B.; Beevers, Sean D.
Abstract: This work presents the first comprehensive real-world emissions results from urban buses retrofitted with an optimised low-NO2 selective catalytic reduction (SCR) system. The SCRT system combines a CRT (Continuously Regenerating Trap) to reduce particle emissions and SCR to reduce NO x emissions. The optimised low-NO2 SCRT was designed to work under urban conditions where the vehicle exhaust gas temperature is often too low for many SCR systems to work efficiently. The system was extensively tested through on-road and test track measurements using a vehicle emission remote sensing instrument capable of measuring both nitric oxide (NO) and nitrogen dioxide (NO2 ). Over 700 on-road measurements of the SCRT system were made in London. Compared with identical buses operating under the same conditions fitted with a CRT, NO2 emissions were reduced by 61% and total NO x by 45%. Under test track conditions reductions in NO x of 77% were observed. The test track results do reveal however that compared with an original Euro III bus without a CRT, the SCRT retrofit bus emissions of NO2 are 50% higher. Engine-out and tailpipe measurements of several important engine parameters under test track conditions showed the important effect of SCR inlet temperature on NO x conversion efficiency. Overall, we conclude that retrofitting urban buses to use low-NO2 SCRT systems is an effective method for delivering NO x and NO2 emissions reduction. Highlights: Use of remote sensing technique to measure in-service NO2 and NOx emissions. Focus on urban-optimised selective catalytic reduction (SCRT) system. On-road and controlled vehicle test track emissions. 45% reduction in NOx and 61% reduction in NO2 cf. non-SCRT buses. Important implications at a European level for meeting NO2 limits.